DEVELOPMENT OF LOCAL INGREDIENT-BASED GLUTEN-FREE DRY NOODLES: THE IMPACT OF BANANA, TAPIOCA, AND RICE FLOUR RATIOS ON PHYSICAL AND SENSORY QUALITIES - Nirmagustina, Dwi Eva; Wirawati, Chandra Utami; Aulia, Cindy; Gusmiati, Devi Marita (LPPM Universitas Jambi, 2026)
Indonesia faces significant wheat import dependency, necessitating the development of healthy, local gluten-free food alternatives for populations with gluten sensitivities. This study aimed to determine the physical, sensory, and chemical characteristics of gluten-free dry noodles made from a ternary blend of Muli banana flour, tapioca, and rice flour. The research followed a factorial Randomized Block Design evaluating three flour formulation ratios and various cooking times. Results indicated that an 8-minute cooking time achieved optimal gelatinization. Formulation R3 (50% banana flour, 20% tapioca flour, and 15% rice flour) emerged as the superior treatment with the highest total rank score of 32 and the lowest cooking loss of 12.48%. Chemical analysis confirmed that moisture (9.59%) and ash content (1.84%) complied with SNI 01-3551-2000 standards, although protein content (1.72%) remained below the 8% threshold. The novelty of this research lies in the strategic optimization of local fruit and tuber starches to overcome technical challenges regarding elasticity and structural integrity inherent in gluten-free products. While phenolic oxidation in banana flour resulted in a darker color, sensory evaluations remained favorable. The implications of these findings suggest that utilizing local non-wheat resources can enhance national food security and provide viable dietary options for health-conscious consumers. Future development should incorporate protein-rich ingredients to improve the nutritional profile.